PERTUMBUHAN BIBIT KRATOM MERAH (Mitragyna speciosa Korth.) DENGAN PEMBERIAN PUPUK ORGANIK CAIR KOTORAN AYAM POTONG - Antoni, Antoni; Zakiah, Zulfa; Mukarlina, Mukarlina (BUANA SAINS, 2023)
The aim of this research was to determine the effect of giving chicken manure liquid organic fertilizer (LOF) on the vegetative growth of kratom plants and to find out the best concentration of chicken manure LOF that can increase plant growth kratom. This study used a completely randomized design which consisted of 7 treatment levels of chicken manure concentration of LOF, namely: control(A1), 50ml/L(A2), 100ml/L(A3), 150ml/L(A4), 200ml/L(A5), 250ml/L(A6), 300ml/L (A7). The results showed that the application of LOF chicken manure had a significant effect on the number of leaves, root dry weight, and shoot dry weight, but had no significant effect on plant height, leaf area, weight root wetness, shoot wet weight and chlorophyll content. The LOF treatment of chicken manure concentration of 150ml/L was the treatment that gave the best results on kratom plant growth for the average number of leaves (16.0 strands), root dry weight (3.94 grams), and shoot dry weight (5.48 grams).